THE RISE OF MULTILINGUALISM IN UZBEKISTAN: IMPLICATIONS FOR ENGLISH LANGUAGE POLICY AND EDUCATION - Zokirova Marjona Xislatjon qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Annotation : This paper examines the growing phenomenon of multilingualism in Uzbekistan and its implications for English language policy and education. As Uzbek society becomes increasingly linguistically diverse due to historical, social, and economic factors, English is gaining prominence as a global lingua franca. The study analyzes how multilingual practices influence language planning, curriculum development, and teaching methodologies in Uzbek schools and universities. It highlights challenges and opportunities for integrating English language learning within a multilingual context, emphasizing the need for inclusive and adaptive language policies to support effective communication and national development.